TINJAUAN YURIDIS PENYELENGGARAAN SEKOLAH BERTARAF INTERNASIONAL PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 5/PUU-X/2012 TENTANG PENGUJIAN UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - Muhammad Taufik; Gusliana '; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Article 50 paragraph (3) of Law Number 20 of 2003 on National Education System is considered by some party violates the mandate of the Constitution of the Republic of Indonesia in 1945. Thus, it is proposed to be tested on the constitutional court. The reason which is appealed by most of parents whose children study in International School is first, the existence of International School violates the duty of the state to educate its people; second, it creates dualism on education system; third, the International School is considered as the new form of liberalization of education; fourth, it tends to create discrimination and caste among those involved in education; and fifth, it potentially could eradicate the identity of Indonesians speaking Bahasa Indonesia.The data used for this study are primary, secondary and tertiary law source, which are collected by literature study.The conclusion of this study is the primary consideration of the Judge of the constitutional institution on the verdict on the existence of International School is that: the understanding and practice which highlight the ability of using foreign language in each education level which potentially deplete the pride of Indonesian language and culture. The law impact that arises is that every thing that relates with International School must be stopped. Further notice of the post-implementation of the constitutional court verdict is final and binding which means there will be no further legal effort.Keywords: Judicial review, The constitutional court verdict Number 5/PUU-X/2012